Structural, Morphological, and Textural Properties of Coprecipitated CaTiO3 for Anion Exchange in the Electrolyzer - Parajuli, D.; Murali, N.; Samatha, K.; Shah, N. L.; Sharma, B. R. (Journal of Nepal Physical Society, 2023)
The limitation in fossil fuel and the emission of greenhouse gases (GHG) resulting in global warming is one of the global challenging issues. Similarly, efficient and cost-effective renewable energy resources are always in demand for the overcome of the limitation. One of the best alternatives to fossil fuels based on renewable energy sources is hydrogen fuel. The main component of the hydrogen fuel generator is the Electrolyzer. Among different types of electrolyzers, the incorporation of an anion exchange membrane is one approach. In this work, we are focusing on the preparation, characterization, and analysis of anion exchange material CaTiO3 used for the electrolyzer. A co-precipitation method was used for the preparation of CaTiO3 XRD shows the orthorhombic structure of the CaTiO3. FT-IR shows the vibrational spectra of CaTiO3. The particles were spherical and crystalline with an average size of 200 nm when viewed through the Scanning Electron Microscope (SEM), Transmission Electron Microscopy (TEM), and High-Resolution Transmission Electron Microscopy (HRTEM). The SAED pattern verifies the single crystalline nature of the sample. In this way, the CaTiO3, the anion exchange agent was synthesized and characterized successfully.